Efecto del fertilizante orgánico “Humus de Lombriz” en el crecimiento y productividad en el cultivo de zucchini (Cucurbita Pepo L.), en el sector Chipe Hamburgo, cantón La Maná, provincia de Cotopaxi. - Alescano Cedeño, Jorge Adrian (2023)
The research project was carried out in the Chipe Hamburgo sector of La Maná canton, whose objective was to evaluate the effect of organic fertilizer "worm humus" on growth and productivity in the cultivation of Zucchini (Cucurbita pepo L.). The first one was applied in different doses in each treatment such as 100g / m², the second of 150g / m² and the third of 200g / m² gave us a total of 450g of humus applied, using a completely randomized block design with 6 replications and 3 treatments, where there were a total of 90 plants in which 12 were taken per treatment, and as a result a quantity of 36 plants that were used in the research, establishing the calculations of economic valuation for the gross income considering the market price in (kg) and of the vegetables multiplied by the total production in (kg), obtained in each one of the treatments to analyze and interpret the total costs, obtaining better results based on the height of the stem (cm), number of flowers, number of leaves, number of fruits per plant, length of the plants, number of flowers, number of leaves, number of fruits per plant, length of the leaves, number of fruits per plant, number of flowers, number of leaves per plant, number of fruits per plant, number of fruits per plant, fruit length (cm) and fruit weight (g), reaching an excellent result to the crop that was used in the treatment T3 Humus with 200g / m² of application, staying above its data variables with the T2 Humus with 150g / m² of application after transplanting until harvesting acquiring a coefficient of variation of 0, 14% in what concerns the final process of production of fruit weight, showing an average result of 1350.00 grams, likewise based on the economic analysis obtained after calculating the cost benefit, the best result was obtained with the T3 Humus with 200g / m² of application, which with an investment of 220.00 USD, reaching an amount of 2.07 USD, that is, 2.07 USD for each dollar invested.